Deciphering the Specificity of Reversible DNA-Phosphate ADP-Ribosylation via the Precise Synthesis and Enzymatic Profiling of Nucleotide-Phospho-ADP-Ribosyl Probes - Lingxiao Liu; Yang Lu; Zongxing Yu; Li Tang; Yidan Wu; Jim Voorneveld; Waghela Deeksha; Dmitri V. Filippov; Ivan Ahel; Qiang Liu (Journal of the American Chemical Society, 2026)
Abstract ADP-ribosylation (ADPr), long recognized as a canonical protein post-translational modification, has recently expanded to include targeting nucleic acids, uncovering a diverse landscape of noncanonical biological functions. Emerging evidence suggests that ADPr at the 5′-phosphate terminus of DNA is implicated in the DNA damage response, yet understanding its precise molecular function has been hampered by the lack of structurally defined chemical probes. Here, we report the stereoselective synthesis of deoxynucleotide-phospho-ADPr (dN-P-ADPr) probes, representing native fragments of terminal DNA-ADPr. Our strategy leverages a mild, stereocontrolled glycosylation to construct the challenging ribosyl-phosphate linkage, followed by P(III)–P(V) coupling to establish the pyrophosphate bridge. This robust toolkit enabled the systematic biochemical profiling of DNA-ADPr hydrolases across diverse kingdoms of life. Remarkably, using these newly developed probes, we uncover hydrolases across the diversity of life capable of reversing ADPr modifications at phosphorylated DNA ends. We further show that these enzymes exhibit an absolute preference for the native-like α-anomer, independent of the identity of the adjacent DNA nucleobase, suggesting that substrate recognition is governed primarily by the ADPr-phosphate linkages rather than the local nucleobase context. Together, these synthetic probes and biochemical insights provide an essential foundation for deciphering the biological landscape of noncanonical ADPr.